Slovensko tekstilstvo skozi čas (obdobje od 1930. do začetka 80-ih let) - Debevc, Jože (University of Maribor Press, 2023)
Slovenian Textile Industry Over Time (the Period from the 1930s to the Beginning of the 80s). In front of you are memories and glimpses, an attempt at a historical record of Slovenian textiles and the people - textile workers, who left their mark on the development of Slovenian textiles in the period from 1930 to the beginning of the 80s.